UNRAVELING THE CONTRIBUTION OF ISLAMIC FINANCE TO ECONOMIC GROWTH WITH INFLATION AS A MEDIATOR - Irfan Aji Pratama; Moh. Mukhsin; Nani Suhartini (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2026)
Indonesia's economic growth over the past twelve years has stagnated between 4–6%, even falling to -2% in 2020. To escape the middle-income trap and achieve high-income status, Indonesia requires consistent growth of around 8% per year. This study examines the impact of SME financing, corporate sukuk, and sharia stocks on Indonesia’s economic growth, using inflation as an intervening variable. Employing a quantitative associative approach with path analysis on time-series data from 2012 to 2023, the study finds that Sharia Stocks and Inflation significantly influence Economic Growth. SME financing significantly affects Inflation, and Sharia Stocks also significantly influence Inflation. Notably, Inflation mediates the relationship between SME financing and Economic Growth, but does not mediate the impact of Corporate Sukuk or Sharia Stocks. These findings highlight the importance of optimizing sharia-compliant financial instruments and inflation management strategies to drive sustainable economic development in Indonesia.